PENGARUH PENGENDALIAN INTERNAL, BUDAYA ORGANISASI DAN KAPABILITAS TERHADAP PENCEGAHAN PENIPUAN LAPORAN KEUANGAN MELALUI AGAMA SEBAGAI VARIABEL INTERVENING DI SKPD SORONG - Irfa Kaharuddin; Mas'ud, Masdar; Amiruddin (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
The aim of this research is to determine the influence of internal control, organizational culture, and ability in preventing fraudulent financial reporting with religiousness as an intervening variable. The sample in this study was a staff member who worked or had worked in the financial department in the Sorong district, which is 103 staff members with non-probability sampling techniques and purposive sampling. Data analysis was used using PLS-SEM (Partial Least Squares-Structural Equation Modeling). The results of the research showed that internal controls, organizational culture, capacity, and religiousness have a significant influence on preventing financial reporting fraud. Organizational culture has a significant impact on reliability, whereas internal control has no significant effect on religiousity. Not much previous research quantitatively reviewed the influence of internal control on religuistas, but some qualitative surveys suggested. In another study (Mohamad Djasuli 2021), besides the five elements and principles of internal control within the COSO framework, it was considered necessary to include one of the principles of the control environment. The principle or focus point referred to is spirituality, religiousness, nature, and style of leadership.